Diabetes and periodontitis: How well are the patients aware about an established relation? - Teja Ummadisetty; Vijay Kumar Chava; Venkata Ramesh Reddy Bhumanapalli (Wolters Kluwer Medknow Publications, 2016)
Aim: The study aimed to assess the levels of awareness about the mutual relationship between diabetes and periodontitis among high-risk age group of the general population and to assess the attitude of general physicians in suggesting diabetic patients to visit a dentist. Materials and Methods: A structured, closed-ended questionnaire either in English or in local language (Telugu) was distributed and collected from 203 patients who were willing to participate in the study attending the Department of Periodontics, Narayana Dental College & Hospital, Nellore, AP. Data were statistically analyzed and represented in percentages and number. Results: Only 49.8% of the sample population knew about the mutual relationship between diabetes and periodontitis and only 46% of the diabetic study population was suggested to visit a dentist by the physician. Conclusion: There is an insufficient knowledge among the diabetic population regarding the mutual relationship. Only few physicians have suggested their diabetic patients to visit a dentist. As diabetic patients tend to visit a physician earlier than a dentist, it is their responsibility to educate and motivate their patients to seek dental treatment.